An evaluation of the Holy Family School High School Library's reference collections and services - Ubana, Rhea Rowena M.; Gonzales, Grace Marie B. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2001)
This study aimed to evaluate the adequacy of the reference collections and sufficiency of the reference services of the Holy Family School (HFS) High School Library in meeting the academic needs of the high school students in each level. It also aims to find out the problems encountered by the students in using the reference collections and services, thereby suggesting solutions for further improvements. Both quantitative and the qualitative methods of evaluation were used. The quantitative methods used were: the absolute size of the reference collections; the growth rate, and; the examination of the number of collections against the minimum standards set by PAASCU and DECS for secondary school libraries. For the qualitative method, the impressionistic approach was used, utilizing survey questionnaires, and observing students' pattern of using the reference collections.
The findings showed that the reference collections of the high school library were very adequate, and the reference services to be very sufficient in responding to the academic demands of the students. Among the problems encountered by the students regarding the collections were obsolescence, incompleteness and unavailability. While in the reference services, the students found the librarian/assistants to be difficult to approach, and unavailable for reference questions.
For the reference collections, it is recommended that the library should acquire or at least update their reference collections specifically the encyclopedia to better answer the needs of the students. These collections should also be available in many formats, not limited to books alone. The installation of computers linked to the Internet, and the acquisition of CD-ROM's are also suggested to extend the reference options of the students. For the reference services, there is no need for additional library personnel, proper scheduling and training of the present staff is needed. Library facilities should also be improved for the preservation of library materials and for a more conducive place for learning. Apart from this, the librarian is advised to formulate a School Library Media Program to further improve the reference collections and services offered in the library. The Holy Family School should also make efforts to help the library aside from monetary support, to live up to the goals of the institution which the library itself is living up to.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: High school libraries -- Reference services. -- Philippines; Holy Family School Library; Reference services (Libraries) -- Evaluation. -- Philippines